KONSEP DASAR PENGEMBANGAN POLA PIKIR PENDIDIK - Afrizal Afrizal (AL-ISHLAH: Jurnal Pendidikan, 2015)
The fuction  of Human Resources (HR) in supporting  the success of organization work is dominant, so  it  should be implemented the increasing of               the Human Resources Continuously. Educator (teacher)  as the main Element of Human Resources and they  they also  have  role to determine the success of the Implementation of Development. The  Educators’ figure must have  adequate Competences. They  includes intellegencies,  attitude and  skills. To run their role optimally,it  need to improve the competence continuously and sustainably. It is usually given by various  exercises, seminars, Scientific Discussion. The activities is done to change the teachers’s mind as State apparatus that have function as  public service